The concept of sustainable development as a methodological base to form strategy for enterprises of oil complex - D. Smirnov (Модернизация, инновация, развитие, 2016)
The article substantiates the need for the enterprises of the oil complex as a methodological basis of their strategy concept of sustainable development, according to which natural resources are treated as natural capital, similar in quality funds. The author of the article analyzed the research of Russian and foreign scientists on the theory of sustainable development from different perspectives, as well as the Concept of the Russian Federation transition to sustainable development, the main criteria for sustainability, particularly management of industrial enterprises in the field of nature and the environment. It was found that the implementation of sustainable development ideas "oil for future generations" is not only a moral and environmental dimension, and financial performance. If companies invest in the exploration work sufficient to sustain growth of proved reserves of raw materials, it will inevitably raise the level of its capitalization.